Brazil: Another lost decade? Domestic policies and attractiveness for foreign capital - Norbert Funke; Peter Nunnenkamp; Rainer Schweickert (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1992)
Formerly a favourite location for private capital inflows, Brazil was virtually cut off from further bank lending in the 1980s. The country's rating in secondary loan markets plummeted, and foreign direct investment dwindled. New external financing was replaced by an accumulation of interest arrears. Retained resources were used for consumption or fueled capital flight, rather than being used for productive investment. Brazil is significantly lagging behind Asian and Latin American competitors in facing the fiercer worldwide competition for foreign capital. The seriously impaired attractiveness in international capital markets is to be attributed to pronounced macroeconomic instability, excessive government interference into goods and factor markets, as well as confrontation with commmercial lenders and restrictive attitudes towards foreign investors. After having lost one decade, Brazil should not risk another one. The country should follow the example of Chile and Mexico, where the implementation of domestic policy reforms was supported by voluntary debt-service concessions of external creditors. This cooperative approach lowered the perception of country risk, led to the repatriation of flight capital, and triggered a favourable investment response. Domestic policy reforms are indispensable for regaining access to international capital markets. The centerpiece of macroeconomic stabilization in Brazil must be to break inflationary expectations through sustained fiscal consolidation. Recent progress in dismantling trade barriers must be supplemented by abandoning the tradition of interventionist price policies in domestic goods markets. The deep-rooted structural deficiencies of labour and financial markets have to be tackled, in order to stimulate human capital formation and enhance efficient financial intermediation.
Keywords: 330; Direktinvestition; Internationale Kapitalmobilität; Auslandsverschuldung; Wirtschaftspolitik; Brasilien; Entwicklungsländer